Ochratoxin A biocontrol and biodegradation by Bacillus subtilis CW 14. (31st December 2013) - Shi, Lei; Liang, Zhihong; Li, Junxia; Hao, Junran; Xu, Yuancong; Huang, Kunlun; Tian, Jingjing; He, Xiaoyun; Xu, Wentao
Abstract BACKGROUND Ochratoxin A (OTA) is a mycotoxin produced by some Aspergillus and Penicillium species. In this study a strain of Bacillus subtilis was tested for its effects on OTA‐producing Aspergillus and OTA degradation. The mechanisms of the effects were also investigated. RESULTS A strain of Bacillus spp. isolated from fresh elk droppings was screened out using the methods described by Guan et al. (Int J Mol Sci 9:1489–1503 (2008)). The 16S rRNA gene sequence suggested that it was B. subtilis CW 14. It could inhibit the growth of the OTA‐producing species Aspergillus ochraceus 3.4412 and Aspergillus carbonarius, with inhibition rates of 33.0 and 33.3% respectively. At 6 µg mL−1 OTA, both viable and autoclaved (121 °C, 20 min) cells of CW 14 bound more than 60% of OTA. In addition, OTA was degraded by the cell‐free supernatant of CW 14. By high‐performance liquid chromatography, the cell‐free supernatant degraded 97.6% of OTA after 24 h of incubation at 30 °C, and no degradation products were produced. The fastest degradation occurred during the first 2 h. In 3 g samples of contaminated maize, 47.1% of OTA was degraded by 50 mL inocula of overnight cultures of CW 14. CONCLUSION These findings indicated that B. subtilis CW 14 could both prevent OTA contamination and degrade OTA in crops. © 2013 Society of Chemical Industry